2018
DOI: 10.1002/mgg3.463
|View full text |Cite
|
Sign up to set email alerts
|

How do genetically disabled adults view selective reproduction? Impairment, identity, and genetic screening

Abstract: The degree to which participants identified with their impairment, more so than how they valued it, was significant in determining attitudes toward selective reproduction. Those who supported genetic screening viewed their impairment as separate to themselves, while participants who considered their impairment as integral to their identity were most likely to report ambivalent or negative attitudes. Policymakers and stakeholders considering the role of genetic carrier screening panels might usefully engage wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 54 publications
(71 reference statements)
2
37
0
Order By: Relevance
“…Ahmed et al, 2015;Barlevy, Wasserman, Stolerman, Erskine, & Dolan, 2012;Chen & Schiffman, 2000;Middleton, Hewison, & Mueller, 1998). These attitudes are influenced by personal attitudes about and experiences with disability, as well as disability identity and involvement with disability culture and community 1 (Boardman & Hale, 2018;Boardman, Young, & Griffiths, 2018;Gollust, Thompson, Gooding, & Biesecker, 2003;Roadhouse et al, 2018;Stern et al, 2002).…”
mentioning
confidence: 99%
“…Ahmed et al, 2015;Barlevy, Wasserman, Stolerman, Erskine, & Dolan, 2012;Chen & Schiffman, 2000;Middleton, Hewison, & Mueller, 1998). These attitudes are influenced by personal attitudes about and experiences with disability, as well as disability identity and involvement with disability culture and community 1 (Boardman & Hale, 2018;Boardman, Young, & Griffiths, 2018;Gollust, Thompson, Gooding, & Biesecker, 2003;Roadhouse et al, 2018;Stern et al, 2002).…”
mentioning
confidence: 99%
“…Recent empirical research by myself and other researchers clearly demonstrate the existence, ethical dilemmas and the ambivalence towards genetic technologies that emerge directly from these two concerns about reprogenetic technologies in the accounts of both genetically and non-genetically disabled people (Boardman 2014). My research has revealed, for example, that the majority of people with genetic disabilities feel that it would be a loss to society to have fewer people with their particular condition coming into the world (Boardman and Hale 2018) and the majority (90%) of family members of people with genetic disabilities such as haemophilia, for example, feel uncomfortable with the idea of pregnancy termination for the condition in their family (Boardman et al 2019).…”
mentioning
confidence: 85%
“…This preliminary conclusion appears to be particularly relevant given that the author herself recognises that the views held by adults with genetic disabilities towards screening and testing vary and can be contradictory (Taneja et al 2004;Boardman and Hale 2018;Barter et al 2017), indicating that some patients look forward to supporting GGE. This group of patients (which I will refer to as B-type patients) may consider that their lives would improve upon the removal of suffering from a concrete condition.…”
mentioning
confidence: 87%